On the use of electrical resistivity method in mapping potential sources and extent of pollution of groundwater systems in Lapai Town, Niger State, Nigeria - Matthew Tersoo Tsepav; Aliyu Yahaya Badeggi; Obaje Nuhu George; Usman Yusuf Tanko; Ibrahim Samuel Ibbi (Journal of Physics: Theories and Applications, 2021)
Electrical resistivity method employing the Schlumberger array was used to occupy forty four (44) vertical electrical sounding points in Lapai town with the aim of determining the depth to aquifers, aquifer thicknesses and aquifer protective capacity. The G41 Geotron resistivity meter was used in obtaining the apparent resistivity data which was processed using Interpex 1XD resistivity interpretation software. The results revealed four lithologic sections which include top lateritic soil, sandy clay, fractured basement and fresh basement. Both confined and unconfined aquifers were identified within the area, with four classes of aquifer proactive capacities as high, moderate, weak and poor. While the aquifer at VES 20 was highly protected, twenty other aquifers were moderately protected, eight others had weak protection and fifteen aquifers were poorly protected. The aquifers were generally of good thicknesses and at varying reasonable depths, making them good reservoirs of water in appreciable quantity. The average aquifer thickness was estimated to be 48.36m while the average depth to aquifers was estimated to be 56.68m.